Lanosidade em pêssegos: aspectos físicó-químico e moleculares - Pegoraro, Camila (2010)
We studied the transcriptional and translational expression of a group of genes associated with cell wall metabolism (Cob, GLS, GalT, CCR, PL, PG, PME, β-Gal, β- Man, α-Ara, Exp1, Exp2, Exp3 and Exp4), endomembrane transport (SFT2, Vap27-2, ADL1A, ROC7, Rab5, Vamp, Kin, Cla, Syn, ERD2 and Rab11), expression of HSPs (HSP40-1er, HSP70er, HSP40-2er, HSPCNX1, HSPCRT2 , HSP70ch, HSP17.8ch, HSP60mi, HSP26.5mi and HSP60-3Bmi) and ethylene synthesis (ACCO) in peaches treated and not treated with gibberellic acid (GA3), monitoring the evolution of ripening and the changes occurred after cold storage (CS) and controlled atmosphere (CA). As variables for characterization of ripening fruit evaluated the production of ethylene, firmness, total acidity (TA), soluble solids (SS), SS / TA ratio and background color of the skin. Initially molecular changes were evaluated in fruit at different maturation stages. Later, the effect of different storage conditions on woolliness development was studied, and finally, the effect of GA3 in delaying maturation and preventing woolliness was evaluated. It was verified that peach ripening is dependent on genes encoding proteins involved in synthesis and degradation of cell wall and proteins involved in the endomembrane transport. Analyzing different forms of storage was observed that the use of controlled atmosphere conditions reduced woolliness, against all expectations, it was found that woolliness is not caused by the reduction in the expression of genes associated with the endomembrane transport. No delay ripening was observed when evaluating the effect of GA3 application prior to pit hardening but help to increase the size and weight of fruit, and decreases the incidence of woolliness in peaches. Increase in fruit size could be explained by the induction of genes encoding expansins and woolliness prevention could be attributed to the induction of genes encoding proteins associated to stress abiotic response, especially HSPs.